A Systematic Review of Screw versus Cement-Retained Fixed Implant Supported Reconstructions - Hamed, Mohamed Tharwat (Clin Cosmet Investig Dent, 2020)
PURPOSE: Dental implant is an effective and standardized treatment procedure in the healthcare setting. This study presents a comparison of dental implant reconstruction using screw and cement. It explicitly reviews the studies concerning cement and screws dental implants to determine the efficiency of the two. PATIENTS AND METHODS: A systematic review was conducted by comprehensively searching electronic literature. The keywords, such as “Screw versus Cement Retained Fixed Implant Supported Reconstructions,” “Screw Retained Fixed Implant.” “Cement Implant” and “Dental Implant” were used for article searching. Twelve studies were included based on the determined inclusion and exclusion criteria. RESULTS: No significant difference was found between the screw-retained and cemented retained implant supported reconstructions. Dental implants are associated with complications leading to implant failure based on the type of restoration that is being used; cement-retained restoration and screw-retained restoration. The treatment selection must be based on the significance criteria and the tooth condition. CONCLUSION: Screw-retained implant-supported reconstructions were found to pose less biological and technological complications. Retention of the tooth is more stable and functional when implantation is selected based on the efficiency of a treatment procedure.